Examining the influence of the pedagogical beliefs on the learning management system usage among university lecturers in the Kurdistan Region of Iraq - Sulaiman, Twana Tahseen; Bali Mahomed, Anuar Shah; Abd Rahman, Azmawani; Hassan, Mazlan (Elsevier, 2022)
The pedagogy method academicians in the Kurdistan Region follow has not been reformed since 1992. There is a need to test different pedagogical beliefs, including constructivist and traditional pedagogical beliefs. This study examined the effect of pedagogical beliefs on technology adoption among university lecturers. The present study extends the Technology Acceptance Model (TAM) by including lecturers' pedagogical beliefs and examining them in Arab counties. A questionnaire was distributed during the COVID-19 pandemic, and 393 data were collected from university lecturers. The study examined how the constructivist and traditional pedagogical beliefs influence the model's three constructs: perceived ease of use, perceived usefulness, and actual use. This study has new finding that contributes to TAM, and the reasons are deliberated.